2007
DOI: 10.1080/14766080709518644
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Research In Management, Spirituality & Religion During Its Founding Years

Abstract: Studying management, spirituality, and religion (MSR) in the workplace involves multi-disciplinary and broadly based literatures. This study utilizes a unique, quantitative visual analysis to explore the disciplinary inclusiveness of MSR in its founding decade from 1996–2005 by examining the population of 231 peer-reviewed empirical MSR-based journal articles. Results show conceptual research construct distinctions within the MSR domain and which disciplines are most represented in the field. The results also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The appreciation and increase of spirituality in the workplace began in the 1990s, and management scholars took notice and began to explore the phenomenon (Ashmos and Duchon 2000, Biberman and Altman 2004, Dean and Fornaciari 2007, Neal and Vallejo 2008. As such, the definition of spirituality in the context of the workplace is formalized as "a framework of organizational values evidenced in the culture that promotes employees' experience of transcendence through the work process, facilitating their sense of being connected in a way that provides feelings of compassion and joy" (Giacalone and Jurkiewicz 2003, p. 13).…”
Section: Introductionmentioning
confidence: 99%
“…The appreciation and increase of spirituality in the workplace began in the 1990s, and management scholars took notice and began to explore the phenomenon (Ashmos and Duchon 2000, Biberman and Altman 2004, Dean and Fornaciari 2007, Neal and Vallejo 2008. As such, the definition of spirituality in the context of the workplace is formalized as "a framework of organizational values evidenced in the culture that promotes employees' experience of transcendence through the work process, facilitating their sense of being connected in a way that provides feelings of compassion and joy" (Giacalone and Jurkiewicz 2003, p. 13).…”
Section: Introductionmentioning
confidence: 99%
“…This paper partially answers the call of scholars within the management, spirituality, and religion (MSR) fields for an in-depth exploration of the relationship between religion, spirituality, and ethics in the workplace (see Dean and Fornaciari 2007). The centrality of ethics in both stakeholder theory and Catholic Social Teaching provides MSR researchers with a useful way to understand how spiritually and religiously infused organizations can succeed in a diverse and globalized world.…”
Section: Discussionmentioning
confidence: 95%
“…In a comprehensive literature review spanning 1996 to 2005 on the "management, spirituality, and religion domain," Dean and Fornaciari (2007) called for further innovative and interdisciplinary empirical research on religion and ethical behavior in organizations owing to the paucity of research in this particular domain. In another Academy of Management study, Weaver and Agle (2002) reported that there have been relatively few empirical studies delineating the interaction of religion and business ethics, and they even went on to assert that inability to discover clear connection between religious role expectations and ethical behavior is analogous to a failure to analyze religious role expectations sufficiently.…”
Section: Literature Reviews Of Research On Religiosity In Edmmentioning
confidence: 99%